Use of ultrasonography for differentiation between bullae and pneumothorax - SANRI, ERKMAN; KARACABEY, SİNAN (SPRINGER HEIDELBERG, 2019)
PurposeModern lung ultrasound (US) is mainly applied not only in critical care, emergency medicine, and trauma surgery, but also in pulmonary and internal medicine. In some cases, pneumothorax (PTX) distinguishes with bullous diseases. In this study, we aimed to discuss the success of US on detecting PTX versus bullae.MethodsWe performed a prospective blinded study. Patients underwent thorax computed tomography (CT) if bullae or pneumothorax could not be differentiated from the chest radiography. An emergency medicine specialist trained in lung US and unaware of x-ray and CT findings performed US. All patients US performed from anterior and lateral wall.ResultsFinal study population included 81 patients. The sensitivity of the presence of pleural sliding in the diagnosis of bullae was 97.50% (86.84-99.94%), and specificity was 100.0% (91.4-100.0%).ConclusionIn conclusion, direct visualisation of ultrasonographic pleural sliding can be a good tool for differentiating bullae and pneumothorax.
Keywords: Bullae; Pneumothorax; Ultrasonography; Emergency; COMET-TAIL ARTIFACT; ULTRASOUND SIGN; BEDSIDE ULTRASOUND; LUNG ULTRASOUND; EPIDEMIOLOGY; DIAGNOSIS; POINT; BLEB; TOOL